Baleen Hydrodynamics and Morphology of Cross-Flow Filtration in Balaenid Whale Suspension Feeding - Werth, Alexander J.; Potvin, Jean (PLOS ONE, 2016)
The traditional view of mysticete feeding involves static baleen directly sieving particles from seawater using a simple, dead-end flow-through filtration mechanism. Flow tank experiments on bowhead (Balaena mysticetus) baleen indicate the long-standing model of dead-end filtration, at least in balaenid (bowhead and right) whales, is not merely simplistic but wrong. To recreate continuous intraoral flow, sections of baleen were tested in a flume through which water and buoyant particles circulated with variable flow velocity. Kinematic sequences were analyzed to investigate movement and capture of particles by baleen plates and fringes. Results indicate that very few particles flow directly through the baleen rack; instead much water flows anteroposteriorly along the interior (lingual) side of the rack, allowing items to be carried posteriorly and accumulate at the posterior of the mouth where they might readily be swallowed. Since water flows mainly parallel to rather than directly through the filter, the cross-flow mechanism significantly reduces entrapment and tangling of minute items in baleen fringes, obviating the need to clean the filter. The absence of copepods or other prey found trapped in the baleen of necropsied right and bowhead whales supports this hypothesis. Reduced through-baleen flow was observed with and without boundaries modeling the tongue and lips, indicating that baleen itself is the main if not sole agent of crossflow. Preliminary investigation of baleen from balaenopterid whales that use intermittent filter feeding suggests that although the biomechanics and hydrodynamics of oral flow differ, cross-flow filtration may occur to some degree in all mysticetes.